Higher dental caries rates and increased cardiovascular disease risk - Roberts, Catherine; Baxter, Dylan J.; Napierala, Dobrawa; Bezamat, Mariana (Frontiers in Oral Health, 2025)
IntroductionEpidemiological studies on the association between dental caries and cardiovascular disease accounting for shared risk factors are inconclusive. This cross-sectional study aimed to determine independent associations between quantitative indices of dental caries including the decayed missing and filled surfaces/ teeth (DMFS/DMFT) and cardiovascular disease in populations from two large dental and medical datasets.MethodsWe used data from the Dental Registry and DNA Repository (DRDR) comprising 2,247 individuals and the National Health and Nutrition Examination Survey (NHANES) that included 3,202 participants. We hypothesized that there would be a significant association between dental caries with cardiovascular disease, when accounting for traditional risk factors. Using R software and STATA, we conducted multiple regression models accounting for risk factors while controlling for multiple testing to determine associations.ResultsThe DRDR participants were more likely to report a history of cardiovascular disease (23.97% vs. 18.06% in the NHANES) and, in general, had higher overall DMFT scores (19.58 vs. 14.78 in the NHANES). After accounting for age, sex, smoking, and ethnicity, DMFS was associated with cardiovascular disease in the DRDR population (p < 0.006), and DMFT was significantly associated with cardiovascular disease in the NHANES dataset (p < 0.0001) accounting for age, sex, smoking, income, periodontal bone loss, and periodontal treatment.ConclusionsOur results show that participants with higher occurrence of dental caries are more likely to have a history of cardiovascular disease independently of traditional risk factors and confounders.Clinical relevanceThe DMFT and DMFS indices could be explored for inclusion in cardiovascular disease prediction tools and future clinical use if causality is established.